Hydroxyapatite particle (HAp) reinforced biodegradable Mg-Zn-Ca metallic glass composite for bio-implant applications. (22nd February 2018) - Ramya, M; Pillai, Mamatha M; Selvakumar, R; Raj, Baldev; Ravi, K R
Abstract: Biodegradable materials suitable for medical application with improved corrosion resistance and good biocompatibility along with enhanced mechanical properties are the need of the hour. Such properties in Mg-Zn-Ca glass forming alloy used as a metal matrix can be obtained through proper reinforcement. Hydroxyapatite (HA) which is a mineral constituent of natural bone has a wide range of medical applications because of its excellent biocompatibility and bioactivity. They promote bone cell adhesion and osteoblastic proliferation. In the present study, the influence of HA particle (HAp ) addition on the glass forming ability, corrosion resistance, mechanical behavior and cytocompatibility of Mg66 Zn30 Ca4 alloy has been investigated. The addition of HAp decreases the glass forming ability of Mg66 Zn30 Ca4 alloy. Significant improvement in corrosion resistance along with marginal improvement in mechanical properties is observed upon addition of HAp . Moreover, HAp incorporation into Mg66 Zn30 Ca4 metallic glass has enhanced the cell viability and cell adhesion of human osteoblast-like cell (MG63) cells, complementing the excellent biocompatibility, bioactivity, osteoconductivity and osteoinductivity of hydroxyapatite mineral due to its biomimetic nature. HA reinforcement is not only a promising approach to improve the corrosion resistance, but also offers a biomimitic interface to enhance osseointegration and overall competence of orthopedic implants.